The importance of complete and high-quality genome sequences in Aspergillus niger research - Ellena, Valeria; Steiger, Matthias G. (Frontiers in Fungal Biology, 2022)
The possibility to sequence the entire genome of an organism revolutionized the fields of biology and biotechnology. The first genome sequence of the important filamentous fungus Aspergillus niger was obtained in 2007, 11 years after the release of the first eukaryotic genome sequence. From that moment, genomics of A. niger has seen major progresses, facilitated by the advances in the sequencing technologies and in the methodologies for gene function prediction. However, there are still challenges to face when trying to obtain complete genomes, equipped with all the repetitive sequences that they contain and without omitting the mitochondrial sequences. The aim of this perspective article is to discuss the current status of A. niger genomics and draw attention to the open challenges that the fungal community should address to move research of this important fungus forward.